2021
DOI: 10.1101/2021.01.24.428008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deconstruction of the retrosplenial granular cortex for social behavior in the mouse model of fragile X syndrome

Abstract: Deficits in fragile X mental retardation 1 protein lead to fragile X syndrome (FXS) with mental retardation and social activity disorder. Until now, the neuronal circuits that mediate the social impairments of FXS were mostly unclear. Accidently, we found fewer c-fos expression in RSG of KO than WT mice after social behavior test. Inactivation of RSG neurons decreased social novelty but not the sociability of naive mice. Interestingly, although the RSG neurons of KO mice had higher background activity, fewer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…These data indicate that SENP1 is a candidate gene for ''ASD predominant gene'' affecting primarily social functions and the RSA region may serve as a circuitry node implicated in regulating mammalian social behaviors. Interestingly, it is recently reported that retrosplenial granular cortex (RSG) is also responsible for social behavior deficits of Fmr1 knockout mice (Shang et al, 2021). Together, these findings support the notion that the retrosplenial cortex plays a critical role in regulating social behaviors of mice.…”
Section: Introductionsupporting
confidence: 66%
“…These data indicate that SENP1 is a candidate gene for ''ASD predominant gene'' affecting primarily social functions and the RSA region may serve as a circuitry node implicated in regulating mammalian social behaviors. Interestingly, it is recently reported that retrosplenial granular cortex (RSG) is also responsible for social behavior deficits of Fmr1 knockout mice (Shang et al, 2021). Together, these findings support the notion that the retrosplenial cortex plays a critical role in regulating social behaviors of mice.…”
Section: Introductionsupporting
confidence: 66%
“…The work by Vesuna et al showed that abnormal elevated neural activity in RSC of mice caused by ketamine treatment led to dissociated behaviors including defects in social interaction in an interesting dose-dependent manner, which strongly implied that neural activity in RSC may play a critical role in salience processing for social interaction of animals (Vesuna et al, 2020). Together with our work and others, we showed that the synaptic transmission in RSC neurons were clearly disrupted in several ASD mice models including Senp1 +/and Fmr1 -/y mice (Shang et al, 2021;Yang et al, 2021). In this work, we proposed a model in which the inhibitory projection from PV-positive neurons of CA1 to RSA serves as a salience processing node to filter out non-social information flowing through RSA from sensory cortices.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, we found that neural activity was abnormally upregulated in RSC of MECP2 overexpressed mouse and functional connectivity of RSC associated with other brain regions were increased in the brain of non-human primate models for ASD, comparing to wild-type (WT) animals (Cai et al, 2020;Yu et al, 2020). Furthermore, our group, together with Li and colleagues, found that excitatory and inhibitory synaptic transmission in RSC are significantly altered in various genetic mouse models of ASD (Shang et al, 2021;Yang et al, 2021). Accumulated evidences suggest that RSC is implicated in regulating social behavior.…”
Section: Introductionmentioning
confidence: 90%